2021
DOI: 10.1371/journal.pone.0244849
|View full text |Cite
|
Sign up to set email alerts
|

Personality types revisited–a literature-informed and data-driven approach to an integration of prototypical and dimensional constructs of personality description

Abstract: A new algorithmic approach to personality prototyping based on Big Five traits was applied to a large representative and longitudinal German dataset (N = 22,820) including behavior, personality and health correlates. We applied three different clustering techniques, latent profile analysis, the k-means method and spectral clustering algorithms. The resulting cluster centers, i.e. the personality prototypes, were evaluated using a large number of internal and external validity criteria including health, locus o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 92 publications
(159 reference statements)
2
16
0
Order By: Relevance
“…In other words, are there certain combinations of Big Five traits — labelled as prototypes — that are more likely to manifest themselves within the personality of individuals? The number of identified prototypes varies between three (Asendorpf et al, 2001 ; Meeus et al, 2011 ), four (Specht, 2014, Gerlach et al, 2018 ), and five (Kerber et al, 2021 ) whereas the empirical evidence tends towards the first number.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, are there certain combinations of Big Five traits — labelled as prototypes — that are more likely to manifest themselves within the personality of individuals? The number of identified prototypes varies between three (Asendorpf et al, 2001 ; Meeus et al, 2011 ), four (Specht, 2014, Gerlach et al, 2018 ), and five (Kerber et al, 2021 ) whereas the empirical evidence tends towards the first number.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…However, regardless of which solution was found, a particular personality type — labelled as the ‘resilient type’ (Asendorpf et al, 2001 ), also called the ‘role model’ (Gerlach et al, 2018 ) — has been clearly identified in all of these studies (for a literature review, see Kerber et al, 2021 ). This prototype is characterized by high values in all Big Five traits.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as introjection constitutes a conflict (i.e., between self-chosen goals and social expectations), the dorsal ACC, which is known as a conflict monitor and error detector beyond others (Carter et al, 1998), may additionally be activated in the representation of unconsciously introjected goals. Also, besides rumination and emotional self-awareness, we explored potential effects of neuroticism and introversion (i.e., low extraversion), as these factors are linked to many psychological conditions, such as depression and anxiety (Kotov et al, 2010), internalizing problems (Kerber et al, 2021), and rumination tendencies (e.g., Roelofs et al, 2008).…”
Section: Neural Correlatesmentioning
confidence: 99%
“…However, a limitation of these studies is that they have focused on one personality measure at a time (see 58 ). A likely possibility is that some personality measures cluster more often together than others, giving rise to personality “profiles” or “types” 59 61 . For example, high extraversion and high conscientiousness tend to cluster together but are both separate from high neuroticism 60 , 62 .…”
Section: Introductionmentioning
confidence: 99%